A comparison of b and uds quark jets to gluon jets - Alexander,G; Allison,J; Altekamp,N; Ametewee,K; Anderson,KJ; Anderson,S; Arcelli,S; Asai,S; Axen,D; Azuelos,G; Ball,AH; Barberio,E; et al. (Zeitschrift Fur Physik C Particles and Fields, 1995)
Symmetric three-jet events are selected from hadronic Z0 decays such that the two lower energy jets are each produced at an angle of about 150° with respect to the highest energy jet. In some cases, a displaced secondary vertex is reconstructed in one of the two lower energy jets, which permits the other lower energy jet to be identified as a gluon jet through anti-tagging. In other cases, the highest energy jet is tagged as a b jet or as a light quark (uds) jet using secondary vertex or track impact parameter and momentum information. Comparing the two lower energy jets of the events with a tag in the highest energy jet to the anti-tagged gluon jets yields a direct comparison of b, uds and gluon jets, which are produced with the same energy of about 24 GeV and under the same conditions. We observe b jets and gluon jets to have similar properties as measured by the angular distribution of particle energy around the jet directions and by the fragmentation functions. In contrast, gluon jets are found to be significantly broader and to have a markedly softer fragmentation function than uds jets. For the k ⊥ jet finder with y cut=0.02, we find Mathematical expression as the ratios of the mean charged particle multiplicity in the gluon jets compared to the b and uds jets. Results are also reported using the cone jet finder. © 1996 Springer-Verlag.